2014
DOI: 10.1007/s10995-014-1475-2
|View full text |Cite
|
Sign up to set email alerts
|

Fish Consumption and Hair Mercury Levels in Women of Childbearing Age, Martin County, Florida

Abstract: The health effects of mercury in humans are mostly on the developing nervous system. Pregnant women and women who are breastfeeding must be targeted in order to decrease mercury exposure to the populations at highest risk-infants, unborn fetuses, and young children. This purpose of this study is to understand the demographics of fish-consumption patterns among women of childbearing age (including pregnant women) in Martin County, Florida, and to analyze the associations of mercury levels in participants' hair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 12 publications
0
9
1
Order By: Relevance
“…In a population-based cohort study of pregnant women in Massachusetts [17], the mean hair mercury concentration was 0.45 µg/g; a majority of participants reported consuming more than two fish servings weekly, higher seafood consumption than reported in the current study. The concentrations reported here are also lower than those reported for women of childbearing age in other studies from Florida; i.e., 0.37 µg/g [18] and 0.56 µg/g [19]. In our earlier study of coastal Florida residents, the mean hair concentration of THg among women was 0.96 ± 0.74 µg/g [7].…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…In a population-based cohort study of pregnant women in Massachusetts [17], the mean hair mercury concentration was 0.45 µg/g; a majority of participants reported consuming more than two fish servings weekly, higher seafood consumption than reported in the current study. The concentrations reported here are also lower than those reported for women of childbearing age in other studies from Florida; i.e., 0.37 µg/g [18] and 0.56 µg/g [19]. In our earlier study of coastal Florida residents, the mean hair concentration of THg among women was 0.96 ± 0.74 µg/g [7].…”
Section: Discussioncontrasting
confidence: 77%
“…Level of educational achievement may be related to knowledge of the beneficial effects of fish consumption on cardiovascular health and other endpoints. An annual income of >$75,000 was significantly associated with Hg concentrations in earlier studies in Florida, USA [18,28]. Income is likely related to the affordability of seafood and relatively expensive fish species.…”
Section: Discussionmentioning
confidence: 89%
“…Mercury can cross the placental barrier and affect the nervous system of the developing fetus [ 6 , 7 , 8 ]. Prenatal exposure to low-level mercury can pose a developmental neurotoxicity to children [ 9 ]. Aside from prenatal exposure to mercury, children may also be exposed to mercury from their diet and breast milk, or from working or living in an environment associated with mercury exposure and hand–to–mouth activities [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Methylmercury exposure often comes from seafood (Karimi et al, 2012; Sheehan et al, 2014). Recent surveys in Florida indicate regional variability in mercury exposures, with a quarter of pregnant women in Martin County showing hair mercury ≥1 μg/g (Nair et al, 2014) but only 7% of participating women between the ages of 18–49 in Duval County showing hair mercury ≥1 pg/g (Traynor et al, 2013). A recent review of calls reporting exposures to the Texas poison control centers found an 89% decrease in exposure-reporting calls from 2000 to 2013 (Forrester, 2016), and national data suggest a decrease of 86% in mercury exposure-report calls between 2000 and 2013 (Litovitz et al, 2001; Mowry et al, 2014).…”
Section: Introductionmentioning
confidence: 99%